Migrating From Face-To-Face to Online Learning During the COVID-19 Pandemic: The Experiences of Psychology Students at a Private Higher Education Institution in Gauteng - Cloete, Monique; Ellington, Jessica Michele; Jansen van Vuuren, Anke; Marais, Elisca Adele; Masinga, Poppy (Central European Journal of Educational Research, 2021)
Due to the COVID-19 pandemic, there was an accelerated migration from face-to-face to online learning. This article aims to explore and describe how psychology students experienced the migration from face-to-face to online learning during the COVID-19 pandemic. It entailed a qualitative research design with an exploratory and descriptive approach. The participants were 28 purposively sampled psychology students from a Private Higher Education Institution in Gauteng. An online survey method was employed to gather the needed information which was then subjected to a thematic analysis. It emerged that the challenges experienced by students were internet connectivity issues, insufficient computer literacy, reduced class time, anxiety, physical impact, and communication issues. Moreover, some benefits related to flexibility, the convenience of online studies and safety from infection with COVID-19 were identified. It was also noted that having certain attributes such as independence, time management skills, having support and being tech savvy improved the online learning process. Some opportunities for Higher Education Institutions to improve the experiences of students included creativity in module delivery as well as providing guidelines on how to use these online platforms.